Berberine Reduces Lipid Accumulation by Promoting Fatty Acid Oxidation in Renal Tubular Epithelial Cells of the Diabetic Kidney - Rong, Qingfeng; Han, Baosheng; Li, Yafeng; Yin, Haizhen; Li, Jing; Hou, Yanjuan (Frontiers in Pharmacology, 2022)
Abnormal lipid metabolism in renal tubular epithelial cells contributes to renal lipid accumulation and disturbed mitochondrial bioenergetics which are important in diabetic kidney disease. Berberine, the major active constituent of Rhizoma coptidis and Cortex phellodendri , is involved in regulating glucose and lipid metabolism. The present study aimed to investigate the protective effects of berberine on lipid accumulation in tubular epithelial cells of diabetic kidney disease. We treated type 2 diabetic db/db mice with berberine (300 mg/kg) for 12 weeks. Berberine treatment improved the physical and biochemical parameters of the db/db mice compared with db/m mice. In addition, berberine decreased intracellular lipid accumulation and increased the expression of fatty acid oxidation enzymes CPT1, ACOX1 and PPAR-α in tubular epithelial cells of db/db mice. The mitochondrial morphology, mitochondrial membrane potential, cytochrome c oxidase activity, mitochondrial reactive oxygen species, and mitochondrial ATP production in db/db mice kidneys were significantly improved by berberine. Berberine intervention activated the AMPK pathway and increased the level of PGC-1α. In vitro berberine suppressed high glucose-induced lipid accumulation and reversed high glucose-induced reduction of fatty acid oxidation enzymes in HK-2 cells. Importantly, in HK-2 cells, berberine treatment blocked the change in metabolism from fatty acid oxidation to glycolysis under high glucose condition. Moreover, berberine restored high glucose-induced dysfunctional mitochondria. These data suggested that berberine alleviates diabetic renal tubulointerstitial injury through improving high glucose-induced reduction of fatty acid oxidation, alleviates lipid deposition, and protect mitochondria in tubular epithelial cells.